2022
DOI: 10.1134/s1990747822010093
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Structural Stability of Erythrocytes by Hydrogen Peroxide: Mathematical Model and Experiment

Abstract: In this study, the regulatory mechanisms induced by extracellular hydrogen peroxide were analyzed on the basis of a mathematical model that considers the key stages of the formation of methemoglobin and ferrylhemoglobin, as well as their binding to the erythrocyte membrane. Numerical modeling has shown that reversible binding of methemoglobin to the membrane is an adaptive mechanism aimed at stabilizing the lipid bilayer of the membrane. On the other hand, an increase in the concentration of ferrylhemoglobin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We have previously shown that the ratio of membrane complexes of various oxidized forms of hemoglobin determined the hormesis dependence of the response of erythrocytes to the action of hydrogen peroxide; namely, it was regulatory at low concentrations and damaging at high concentrations [14]. The range of hydrogen peroxide concentrations at which an increase in the structural stability of the membrane (the hormesis region) was observed depended on a number of internal and external factors.…”
Section: Cell Biophysicsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that the ratio of membrane complexes of various oxidized forms of hemoglobin determined the hormesis dependence of the response of erythrocytes to the action of hydrogen peroxide; namely, it was regulatory at low concentrations and damaging at high concentrations [14]. The range of hydrogen peroxide concentrations at which an increase in the structural stability of the membrane (the hormesis region) was observed depended on a number of internal and external factors.…”
Section: Cell Biophysicsmentioning
confidence: 99%
“…The protective properties of cells during hemolysis are determined by the structural stability of the membrane and are characterized by the protection coefficient k p . Based on previous studies [14], the model assumed that the structural stability of the membrane depended on the number of membrane complexes of methemoglobin and ferryl hemoglobin and changes over time.…”
Section: Description Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation